Farmer Satisfaction with Dipanen Pro Auction App: Kepuasan Petani terhadap Aplikasi Lelang Dipanen Pro - Indah Setiawati; Lulus Ika Riswiana; Muhamad Baewodi; Arief Kelik Nugroho; Eka Purna Yudha; Muhammad Nur Choirul Afif (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The agricultural sector, especially horticulture, plays a vital role in Indonesia’s economy, yet chili farmers face persistent market volatility due to long distribution chains and price disparities. Specific Background: In Karangrejo, Kulon Progo, the introduction of the Dipanen Pro application aimed to provide an equitable and transparent digital auction system to streamline chili marketing. Knowledge Gap: While digital market innovations exist, empirical studies examining user satisfaction and trust from farmers' perspectives—especially on auction apps like Dipanen Pro—remain scarce. Aims: This study assesses the satisfaction of chili farmers using Dipanen Pro and identifies critical factors influencing their perceptions. Results: Using a survey of 30 active users and descriptive statistical analysis, the study found overall satisfaction across five SERVQUAL dimensions—tangibles, empathy, reliability, responsiveness, and assurance—with the highest score in assurance (RK = 4.5) and the lowest in reliability (RK = 3.8). Novelty: The study highlights reliability as a persistent challenge, suggesting that technical stability and transactional security remain pivotal for long-term adoption despite general user satisfaction. Implications: Findings provide valuable insights for platform developers and policymakers to refine auction-based agricultural marketing, particularly by strengthening digital reliability and building sustained user trust for rural farming communities. Highlights: Farmers report high satisfaction with Dipanen Pro, especially in service assurance. Reliability is the weakest factor, requiring urgent technical improvement. The study emphasizes user trust as crucial for sustaining digital agricultural platforms. Keywords: auction market, chili, digital marketing, farmer satisfaction, rural technology